Scroll:set and function >> Exercice 1.3 >> saq (4261)


Written Instructions:

For each Multiple Choice Question (MCQ), four options are given. One of them is the correct answer. Make your choice (1,2,3 or 4). Write your answers in the brackets provided..

For each Short Answer Question(SAQ) and Long Answer Question(LAQ), write your answers in the blanks provided.

Leave your answers in the simplest form or correct to two decimal places.



 

1)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {2,3,4}, B = {3,4,5,6} and C = {4,5,6,7}

 n(A∪B∪C) =


Answer:_______________




2)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {q,s,k,d,r}, B = {o,q,s} and C = {q,r,o}

 n(A∪B∪C) =



Answer:_______________




3)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {5,6,7}, B = {6,7,8,9} and C = {7,8,9,10}

 n(A∪B∪C) =


Answer:_______________




4)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {j,a,c,u,h}, B = {y,b,q} and C = {j,h,y}

 n(A∪B∪C) =



Answer:_______________




5)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {3,4,5}, B = {4,5,6,7} and C = {5,6,7,8}

 n(A∪B∪C) =


Answer:_______________




6)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {t,s,j,e,u}, B = {y,b,r} and C = {t,u,y}

 n(A∪B∪C) =



Answer:_______________




7)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {6,7,8}, B = {7,8,9,10} and C = {8,9,10,11}

 n(A∪B∪C) =


Answer:_______________




8)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {u,n,r,z,l}, B = {h,w,u} and C = {u,l,h}

 n(A∪B∪C) =



Answer:_______________




9)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {4,5,6}, B = {5,6,7,8} and C = {6,7,8,9}

 n(A∪B∪C) =


Answer:_______________




10)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {q,s,p,t,w}, B = {l,m,o} and C = {q,w,l}

 n(A∪B∪C) =



Answer:_______________




 

1)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {2,3,4}, B = {3,4,5,6} and C = {4,5,6,7}

 n(A∪B∪C) = Answer: 6


SOLUTION 1 :

 Given : 

A = {2,3,4}, B = {3,4,5,6} and C = {4,5,6,7}

⇒          n(A) = 3, n(B) = 4, n(C) = 4

(A∩B) =  {2,3,4} ∩ {3,4,5,6}

           = {3,4}

⇒       n(A∩B) = 2

 (B∩C) = {3,4,5,6} ∩  {4,5,6,7}

           =  {4,5,6}

⇒     n(B∩C)  = 3

 (AC)  = {2,3,4} ∩ {4,5,6,7}

            = {4}

⇒       n(A∩C) = 1

(A∪B∪C) = [{2,3,4} ∪ {3,4,5,6}∪ {4,5,6,7}]

               = {2,3,4,5,6}∪{4,5,6,7}

        = {2,3,4,5,6,7}

⇒     n(A∪B∪C) = 6      ...............  (1)

(A∩B∩C) = [{2,3,4} ∩ {3,4,5,6} ∩ {4,5,6,7}]

                  = {3,4} ∩ {4,5,6,7}

                  = {4}

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 3 + 4 + 4 - 2 - 3 - 1 + 1

                       = 12 - 6 = 6      ...............  (2)

From (1) and (2), It is true for given sets. 

 



2)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {f,r,n,a,p}, B = {z,x,n} and C = {f,p,z}

 n(A∪B∪C) = Answer: 8


SOLUTION 1 :

  Given : 

A = {f,r,n,a,p}, B = {z,x,n} and C = {f,p,z}

⇒          n(A) = 5, n(B) = 3, n(C) = 3

(A∩B) =  {f,r,n,a,p} ∩ {z,x,n}

           = { }

⇒       n(A∩B) = 0

 (B∩C) = {z,x,n} ∩ {f,p,z}

           =  {z}

⇒     n(B∩C)  = 1

 (AC)  = {f,r,n,a,p} ∩ {f,p,z}

            = {f,p}

⇒       n(A∩C) = 2

(A∪B∪C) = [{f,r,n,a,p} ∪ {z,x,n}∪{f,p,z}

               = {f,r,n,a,p,z,x,n}∪{f,p,z}

        = {f,r,n,a,p,z,x,n}

⇒     n(A∪B∪C) = 8     ...............  (1)

(A∩B∩C) = [{f,r,n,a,p} ∩ {z,x,n} ∩ {f,p,z}]

                  = { } ∩ {n,a,p,z}

                  = { }

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 5 + 3 + 3 - 0 - 1 - 2 + 0

                       = 11 - 3 = 8      ...............  (2)

From (1) and (2), It is true for given sets. 

 



3)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {5,6,7}, B = {6,7,8,9} and C = {7,8,9,10}

 n(A∪B∪C) = Answer: 6


SOLUTION 1 :

 Given : 

A = {5,6,7}, B = {6,7,8,9} and C = {7,8,9,10}

⇒          n(A) = 3, n(B) = 4, n(C) = 4

(A∩B) =  {5,6,7} ∩ {6,7,8,9}

           = {6,7}

⇒       n(A∩B) = 2

 (B∩C) = {6,7,8,9} ∩  {7,8,9,10}

           =  {7,8,9}

⇒     n(B∩C)  = 3

 (AC)  = {5,6,7} ∩ {7,8,9,10}

            = {7}

⇒       n(A∩C) = 1

(A∪B∪C) = [{5,6,7} ∪ {6,7,8,9}∪ {7,8,9,10}]

               = {5,6,7,8,9}∪{7,8,9,10}

        = {5,6,7,8,9,10}

⇒     n(A∪B∪C) = 6      ...............  (1)

(A∩B∩C) = [{5,6,7} ∩ {6,7,8,9} ∩ {7,8,9,10}]

                  = {6,7} ∩ {7,8,9,10}

                  = {7}

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 3 + 4 + 4 - 2 - 3 - 1 + 1

                       = 12 - 6 = 6      ...............  (2)

From (1) and (2), It is true for given sets. 

 



4)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {l,e,o,t,k}, B = {v,w,x} and C = {l,k,v}

 n(A∪B∪C) = Answer: 8


SOLUTION 1 :

  Given : 

A = {l,e,o,t,k}, B = {v,w,x} and C = {l,k,v}

⇒          n(A) = 5, n(B) = 3, n(C) = 3

(A∩B) =  {l,e,o,t,k} ∩ {v,w,x}

           = { }

⇒       n(A∩B) = 0

 (B∩C) = {v,w,x} ∩ {l,k,v}

           =  {v}

⇒     n(B∩C)  = 1

 (AC)  = {l,e,o,t,k} ∩ {l,k,v}

            = {l,k}

⇒       n(A∩C) = 2

(A∪B∪C) = [{l,e,o,t,k} ∪ {v,w,x}∪{l,k,v}

               = {l,e,o,t,k,v,w,x}∪{l,k,v}

        = {l,e,o,t,k,v,w,x}

⇒     n(A∪B∪C) = 8     ...............  (1)

(A∩B∩C) = [{l,e,o,t,k} ∩ {v,w,x} ∩ {l,k,v}]

                  = { } ∩ {o,t,k,v}

                  = { }

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 5 + 3 + 3 - 0 - 1 - 2 + 0

                       = 11 - 3 = 8      ...............  (2)

From (1) and (2), It is true for given sets. 

 



5)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {3,4,5}, B = {4,5,6,7} and C = {5,6,7,8}

 n(A∪B∪C) = Answer: 6


SOLUTION 1 :

 Given : 

A = {3,4,5}, B = {4,5,6,7} and C = {5,6,7,8}

⇒          n(A) = 3, n(B) = 4, n(C) = 4

(A∩B) =  {3,4,5} ∩ {4,5,6,7}

           = {4,5}

⇒       n(A∩B) = 2

 (B∩C) = {4,5,6,7} ∩  {5,6,7,8}

           =  {5,6,7}

⇒     n(B∩C)  = 3

 (AC)  = {3,4,5} ∩ {5,6,7,8}

            = {5}

⇒       n(A∩C) = 1

(A∪B∪C) = [{3,4,5} ∪ {4,5,6,7}∪ {5,6,7,8}]

               = {3,4,5,6,7}∪{5,6,7,8}

        = {3,4,5,6,7,8}

⇒     n(A∪B∪C) = 6      ...............  (1)

(A∩B∩C) = [{3,4,5} ∩ {4,5,6,7} ∩ {5,6,7,8}]

                  = {4,5} ∩ {5,6,7,8}

                  = {5}

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 3 + 4 + 4 - 2 - 3 - 1 + 1

                       = 12 - 6 = 6      ...............  (2)

From (1) and (2), It is true for given sets. 

 



6)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {b,a,p,c,g}, B = {t,s,c} and C = {b,g,t}

 n(A∪B∪C) = Answer: 8


SOLUTION 1 :

  Given : 

A = {b,a,p,c,g}, B = {t,s,c} and C = {b,g,t}

⇒          n(A) = 5, n(B) = 3, n(C) = 3

(A∩B) =  {b,a,p,c,g} ∩ {t,s,c}

           = { }

⇒       n(A∩B) = 0

 (B∩C) = {t,s,c} ∩ {b,g,t}

           =  {t}

⇒     n(B∩C)  = 1

 (AC)  = {b,a,p,c,g} ∩ {b,g,t}

            = {b,g}

⇒       n(A∩C) = 2

(A∪B∪C) = [{b,a,p,c,g} ∪ {t,s,c}∪{b,g,t}

               = {b,a,p,c,g,t,s,c}∪{b,g,t}

        = {b,a,p,c,g,t,s,c}

⇒     n(A∪B∪C) = 8     ...............  (1)

(A∩B∩C) = [{b,a,p,c,g} ∩ {t,s,c} ∩ {b,g,t}]

                  = { } ∩ {p,c,g,t}

                  = { }

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 5 + 3 + 3 - 0 - 1 - 2 + 0

                       = 11 - 3 = 8      ...............  (2)

From (1) and (2), It is true for given sets. 

 



7)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {6,7,8}, B = {7,8,9,10} and C = {8,9,10,11}

 n(A∪B∪C) = Answer: 6


SOLUTION 1 :

 Given : 

A = {6,7,8}, B = {7,8,9,10} and C = {8,9,10,11}

⇒          n(A) = 3, n(B) = 4, n(C) = 4

(A∩B) =  {6,7,8} ∩ {7,8,9,10}

           = {7,8}

⇒       n(A∩B) = 2

 (B∩C) = {7,8,9,10} ∩  {8,9,10,11}

           =  {8,9,10}

⇒     n(B∩C)  = 3

 (AC)  = {6,7,8} ∩ {8,9,10,11}

            = {8}

⇒       n(A∩C) = 1

(A∪B∪C) = [{6,7,8} ∪ {7,8,9,10}∪ {8,9,10,11}]

               = {6,7,8,9,10}∪{8,9,10,11}

        = {6,7,8,9,10,11}

⇒     n(A∪B∪C) = 6      ...............  (1)

(A∩B∩C) = [{6,7,8} ∩ {7,8,9,10} ∩ {8,9,10,11}]

                  = {7,8} ∩ {8,9,10,11}

                  = {8}

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 3 + 4 + 4 - 2 - 3 - 1 + 1

                       = 12 - 6 = 6      ...............  (2)

From (1) and (2), It is true for given sets. 

 



8)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {w,g,p,s,c}, B = {q,h,m} and C = {w,c,q}

 n(A∪B∪C) = Answer: 8


SOLUTION 1 :

  Given : 

A = {w,g,p,s,c}, B = {q,h,m} and C = {w,c,q}

⇒          n(A) = 5, n(B) = 3, n(C) = 3

(A∩B) =  {w,g,p,s,c} ∩ {q,h,m}

           = { }

⇒       n(A∩B) = 0

 (B∩C) = {q,h,m} ∩ {w,c,q}

           =  {q}

⇒     n(B∩C)  = 1

 (AC)  = {w,g,p,s,c} ∩ {w,c,q}

            = {w,c}

⇒       n(A∩C) = 2

(A∪B∪C) = [{w,g,p,s,c} ∪ {q,h,m}∪{w,c,q}

               = {w,g,p,s,c,q,h,m}∪{w,c,q}

        = {w,g,p,s,c,q,h,m}

⇒     n(A∪B∪C) = 8     ...............  (1)

(A∩B∩C) = [{w,g,p,s,c} ∩ {q,h,m} ∩ {w,c,q}]

                  = { } ∩ {p,s,c,q}

                  = { }

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 5 + 3 + 3 - 0 - 1 - 2 + 0

                       = 11 - 3 = 8      ...............  (2)

From (1) and (2), It is true for given sets. 

 



9)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {4,5,6}, B = {5,6,7,8} and C = {6,7,8,9}

 n(A∪B∪C) = Answer: 6


SOLUTION 1 :

 Given : 

A = {4,5,6}, B = {5,6,7,8} and C = {6,7,8,9}

⇒          n(A) = 3, n(B) = 4, n(C) = 4

(A∩B) =  {4,5,6} ∩ {5,6,7,8}

           = {5,6}

⇒       n(A∩B) = 2

 (B∩C) = {5,6,7,8} ∩  {6,7,8,9}

           =  {6,7,8}

⇒     n(B∩C)  = 3

 (AC)  = {4,5,6} ∩ {6,7,8,9}

            = {6}

⇒       n(A∩C) = 1

(A∪B∪C) = [{4,5,6} ∪ {5,6,7,8}∪ {6,7,8,9}]

               = {4,5,6,7,8}∪{6,7,8,9}

        = {4,5,6,7,8,9}

⇒     n(A∪B∪C) = 6      ...............  (1)

(A∩B∩C) = [{4,5,6} ∩ {5,6,7,8} ∩ {6,7,8,9}]

                  = {5,6} ∩ {6,7,8,9}

                  = {6}

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 3 + 4 + 4 - 2 - 3 - 1 + 1

                       = 12 - 6 = 6      ...............  (2)

From (1) and (2), It is true for given sets. 

 



10)  

 verify n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C) + n(A∩B∩C)  for the sets given below :

(i) A = {r,x,o,e,h}, B = {k,i,d} and C = {r,h,k}

 n(A∪B∪C) = Answer: 8


SOLUTION 1 :

  Given : 

A = {r,x,o,e,h}, B = {k,i,d} and C = {r,h,k}

⇒          n(A) = 5, n(B) = 3, n(C) = 3

(A∩B) =  {r,x,o,e,h} ∩ {k,i,d}

           = { }

⇒       n(A∩B) = 0

 (B∩C) = {k,i,d} ∩ {r,h,k}

           =  {k}

⇒     n(B∩C)  = 1

 (AC)  = {r,x,o,e,h} ∩ {r,h,k}

            = {r,h}

⇒       n(A∩C) = 2

(A∪B∪C) = [{r,x,o,e,h} ∪ {k,i,d}∪{r,h,k}

               = {r,x,o,e,h,k,i,d}∪{r,h,k}

        = {r,x,o,e,h,k,i,d}

⇒     n(A∪B∪C) = 8     ...............  (1)

(A∩B∩C) = [{r,x,o,e,h} ∩ {k,i,d} ∩ {r,h,k}]

                  = { } ∩ {o,e,h,k}

                  = { }

⇒ n(A∩B∩C) = 1

∴  n(A∪B∪C) = n(A) + n(B) + n(C) - n(A∩B) - n(B∩C) - n(A∩C)

                         + n(A∩B∩C)

                        = 5 + 3 + 3 - 0 - 1 - 2 + 0

                       = 11 - 3 = 8      ...............  (2)

From (1) and (2), It is true for given sets.